2017
DOI: 10.1021/acs.jproteome.6b00833
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Proteomics Predicts a Sustained Complete-Response after Transarterial Chemoembolization and Clinical Outcomes in Patients with Hepatocellular Carcinoma: A Prospective Cohort Study

Abstract: This study was aimed to identify blood-based biomarkers to predict a sustained complete response (CR) after transarterial chemoembolization (TACE) using targeted proteomics. Consecutive patients with HCC who had undergone TACE were prospectively enrolled (training (n = 100) and validation set (n = 80)). Serum samples were obtained before and 6 months after TACE. Treatment responses were evaluated using the modified Response Evaluation Criteria in Solid Tumors (mRECIST). In the training set, the MRM-MS assay id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…It is closely related to immune function and is highly expressed in normal human lung tissues but lowly expressed in lung cancer tissues (Hummelshoj et al, 2008). LUAD and LIHC patients with low expression of FCN3 have poor prognosis, which is consistent with the findings in liver cancer and esophageal cancer (Yu et al, 2017;. Carbonic anhydrase (CA4) is zinc metalloenzyme that catalyzes the reversible hydration of carbon dioxide.…”
Section: Discussionsupporting
confidence: 64%
“…It is closely related to immune function and is highly expressed in normal human lung tissues but lowly expressed in lung cancer tissues (Hummelshoj et al, 2008). LUAD and LIHC patients with low expression of FCN3 have poor prognosis, which is consistent with the findings in liver cancer and esophageal cancer (Yu et al, 2017;. Carbonic anhydrase (CA4) is zinc metalloenzyme that catalyzes the reversible hydration of carbon dioxide.…”
Section: Discussionsupporting
confidence: 64%
“…However, use of these two pathological markers would require biopsy analysis prior to TACE. Another study identified a panel of pre-TACE serum protein markers (including AFP, PIVKA-II level, LRG1, APCS, BCHE, C7, and FCN3) that can help predict TACE response of HCC (48). These factors can be investigated further to improve response prediction accuracy and HCC patient selection for TACE.…”
Section: Discussionmentioning
confidence: 99%
“…44 Higher serum C7 protein level of HCC has been proposed as an indicator of poor response to transarterial chemoembolization. 45 Both PIGU and HNRNPC have been confirmed to be overexpressed in HCC and the high expression level of these 2 genes is associated with unfavorable prognosis. 46,47 In addition, MIMAT0004677 plays an oncogenic role in HCC through promoting cancer progression by directly targeting NCKAP1 and low expression of MIMAT0004677 is an indicator of favorable survival.…”
Section: Discussionmentioning
confidence: 99%